2021
DOI: 10.3390/microorganisms9061225
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fermentation Parameters and Bacterial Community in High-Moisture Alfalfa Silage with or without Lactic Acid Bacteria

Abstract: The aim of this study was to gain deeper insights into the dynamics of fermentation parameters and the bacterial community during the ensiling of high-moisture alfalfa. A commercial lactic acid bacteria (YX) inoculant was used as an additive. After 15 and 30 days of ensiling, the control silage (CK) exhibited a high pH and a high concentration of ammoniacal nitrogen (NH3-N); Enterobacter and Hafnia-Obesumbacterium were the dominant genera. At 60 d, the pH value and the concentration of NH3-N in CK silage incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…However, inhibiting the population of Hafnia-Obesumbacterium seems to be a difficult task. Zhao et al (2021) found that the commercial LAB inoculants notably enhanced the production of lactic acid and reduced pH values but cannot suppress the flourishment of Hafnia-Obesumbacterium . Hence, the research about controlling the Hafnia-Obesumbacterium population in silages needs to be further conducted.…”
Section: Discussionmentioning
confidence: 99%
“…However, inhibiting the population of Hafnia-Obesumbacterium seems to be a difficult task. Zhao et al (2021) found that the commercial LAB inoculants notably enhanced the production of lactic acid and reduced pH values but cannot suppress the flourishment of Hafnia-Obesumbacterium . Hence, the research about controlling the Hafnia-Obesumbacterium population in silages needs to be further conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in DM content during ensiling was due to the activity of undesirable bacteria, which metabolized soluble carbohydrates to CO 2 , causing DM losses ( Ávila et al, 2014 ), while the severe decline in DM in KN90S during 7 days of fermentation was due to effluent production. High-moisture silage often bears a high risk of effluent production, leading to high DM loss ( Zhao et al, 2021 ), and the peak effluent of silage typically occurs within 10 days after ensiling given the time required for plant cell to rupture ( Gebrehanna et al, 2014 ). This is consistent with the view of Savoie et al (2002) , who found that the amount of daily effluent collected from the timothy silage was relatively high within 7 days of ensiling, and the effluent flow declined in subsequent days.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in culture‐independent analyses, such as high‐throughput sequencing technology, have enabled microbial communities to be defined with a degree of detail that is impossible using classical microbiology (Dong, Li, Chen, Wang, & Shao, 2019). Understanding of the microbial communities involved in the ensiling process would provide an insight into approaches to improve the forage conservation (Tian et al, 2021; Zhao et al, 2021). Therefore, the objective of this study was to investigate the effects of different additives on the fermentation quality and bacterial community of high‐moisture WPQ silage.…”
Section: Introductionmentioning
confidence: 99%